New insights into the cardiorespiratory physiology of weaned southern elephant seals (Mirounga leonina) - CR Cummings; M Lea; MG Morrice; S Wotherspoon; MA Hindell (2015)
Southern elephant seal (Mirounga leonina) pups must strike a balance between conserving energy during their post-weaning fast and simultaneously developing diving abilities to attain nutritional independence. Little is known about environmental influences on cardiorespiratory patterns, hence energy use, throughout the 6 week fast. Continuous heart rates were recorded for free-ranging, newly weaned southern elephant seals using heart rate time-depth recorders for 5-9 days at Sub-Antarctic Macquarie Island, during October 1994 (n = 1), 1995 (n = 4) and 1996 (n = 1). Daytime observations of respiration and behaviour were made throughout. We present the first instance of synchronous heart rate traces recorded simultaneously for individual weaners. Generalized additive models revealed that a sinusoidal pattern of diurnal heart rate elevation and nocturnal depression was evident in all seals and, on at least one occasion, a conspicuous break in this pattern coincided with an extreme cold weather event. Seals in this study were capable of considerable cardiorespiratory control and regularly demonstrated bradycardia during periods of resting apnoea. Apnoeic duration ranged from 33 to 291 s (mean 134 s). Apnoeic heart rates (mean 67 ± 15 beats min(-1), range 40-114 beats min(-1)) were on average 19.7% lower than those exhibited during periods of eupnoea (mean 83 ± 15 beats min(-1), range 44-124 beats min(-1)). The early development of the cardiorespiratory response is characterized by arrhythmic heart and respiration rates. The strong temporal patterns observed are being driven by the opposing requirements of maximizing time spent fasting in order to develop diving capabilities and of maximizing departure mass. This pilot study has highlighted a potentially large effect of ambient weather conditions on newly weaned southern elephant seal cardiorespiratory activity. Given the increasing westerlies and more erratic and increasing storminess associated with the Southern Annular Mode predicted in the Southern Ocean, the ...